Hubungan Karakteristik Klinis dengan Gambaran Histopatologi Pasien Karsinoma Sel Basal di RSUD Dr. Moewardi Surakarta - Sugih Primas Adjie; Prasetyadi Mawardi; Nugrohoaji Dharmawan; Indah Julianto (Riviera Publishing, 2025)
Basal cell carcinoma (BCC) is the most common non-melanoma skin cancer, with varying clinical and histopathological manifestations. The infiltrative nature of BCC affects tumor aggressiveness and its prognosis. In Indonesia, data regarding the relationship between clinical characteristics and histopathological features of BCC are still limited. This study aims to analyze the relationship between clinical characteristics and the infiltrative nature in BCC patients at Dr. Moewardi General Hospital, Surakarta. A retrospective cross-sectional study used medical records and paraffin blocks of BCC patients diagnosed from January 2021 to February 2025. The evaluated characteristics included age, sex, anatomical location, lesion size, and histopathological subtypes. Histopathological features were analyzed based on infiltrative and non-infiltrative tumor characteristics. Of the 29 patients analyzed, the majority were female (55.2%) with a median age of 57 years. Most lesions were ?2 cm² (82.8%) and located on the middle face (75.9%). The dominant histopathological subtypes were nodulo-ulcerative (41.4%) and nodular (34.4%). Only 48.3% of cases were infiltrative. No significant relationship was found between clinical characteristics and the infiltrative nature of the tumor, emphasizing the importance of histopathological evaluation in determining tumor aggressiveness. These findings are essential for the development of diagnostic and therapeutic strategies for BCC in Indonesia.